2020
DOI: 10.1155/2020/5640960
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Recurrences of Genital Herpes Are Associated with Enhanced Systemic HSV-Specific T Cell Response

Abstract: Objectives. Genital herpes simplex virus (HSV) infection is controlled by HSV-specific T cells in the genital tract, and the role of systemic T cell responses is not fully understood. Thus, we analysed T cell responses in patients with recurrent genital herpes (GH). Methods. T cell responses to HSV-1 and HSV-2 native antigens and the expression of HLA-DR and CD38 molecules on circulating CD8+ T cells were analysed in adults with high frequency of GH recurrences (19 patients) and low frequency of GH recurrences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…These approaches will likely demonstrate varied efficacy in clinical trials; although, they have demonstrated high efficacy in preclinical animal models. It is important to note that there were reports that an exacerbated CD8+T cell response through repeated reactivation may increase the rate of reactivation [ 87 ]. Therefore, an effective vaccine approach is required to protect without exacerbating the reactivation of the latent virus, suggesting that both inflammatory and immune-regulatory pathways and cellular milieus must be considered.…”
Section: Clinical Trials Of Herpes Simplex Vaccinesmentioning
confidence: 99%
“…These approaches will likely demonstrate varied efficacy in clinical trials; although, they have demonstrated high efficacy in preclinical animal models. It is important to note that there were reports that an exacerbated CD8+T cell response through repeated reactivation may increase the rate of reactivation [ 87 ]. Therefore, an effective vaccine approach is required to protect without exacerbating the reactivation of the latent virus, suggesting that both inflammatory and immune-regulatory pathways and cellular milieus must be considered.…”
Section: Clinical Trials Of Herpes Simplex Vaccinesmentioning
confidence: 99%